Blockchain and the Evolution of Decentralized Finance Navigating Growth and Vulnerabilities - Yusuf Durachman; Abdul Wahab Abdul Rahman (Journal of Current Research in Blockchain, 2024)
Decentralized Finance (DeFi) is revolutionizing the way individuals and institutions engage with financial services by removing intermediaries and offering decentralized alternatives to traditional banking and finance systems. This paper explores the rapid growth and impact of DeFi on global financial systems, focusing on key protocols such as Uniswap, Aave, and Compound. Using both qualitative and quantitative methodologies, including case studies and comparative analyses, the research examines the evolution of DeFi in terms of Total Value Locked (TVL), transaction costs, security challenges, and user adoption. The findings reveal that DeFi platforms have experienced exponential growth in liquidity, with TVL across major protocols increasing from $50 million in January 2020 to over $100 billion by January 2024. Uniswap alone saw its TVL grow from $50 million to $15 billion during the same period. DeFi significantly reduces transaction costs, with cross-border fees averaging $7 on Uniswap, compared to $35 in traditional banks. However, Ethereum gas fees remain volatile, exceeding $50 during peak congestion periods. Despite these cost benefits, the study also identifies security as a major concern, with 22 significant security incidents reported in DeFi between 2020 and 2023, resulting in substantial financial losses. Additionally, the lack of clear regulatory frameworks continues to pose challenges to broader adoption. This research concludes that while DeFi has the potential to disrupt traditional financial systems, its long-term success depends on addressing these technical and regulatory challenges. The adoption of Layer-2 scaling solutions, along with improvements in security and regulatory clarity, will be essential for ensuring the continued growth and stability of the DeFi ecosystem.